SELF-MONITORING STRATEGY IN IMPROVING STUDENTS’ ABILITY IN USING SIMPLE PAST TENSE IN RECOUNT TEXT - Priyatni, Jeng Anggi; Aprilliaswati, Rahayu; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was conducted in order to know how the implementation of the Self-Monitoring Strategy (SMS) improved students’ ability in using simple past tense in recount text to the 10th-grade students of SMAN 1 Pontianak in academic year 2018/2019. This research had been done through Classroom Action Research (CAR) in three cycles. The subjects of this research were the tenth grade English teacher and 36 students of year-10 Science Program 9 of SMAN 1 Pontianak. In collecting the data, the researcher used field notes, observation checklist, and students’ individual assessments. The result showed that the implementation of the SMS step 1 (selecting target behavior), step 2 (knowing what is easy and difficult), and step 5 (evaluation) improve students’ motivation, activeness, and self-awareness of their own learning. Furthermore, the implementation of SMS step 3 (recognition about the mistake they make) and 4 (adjusting the work) improve students’ ability in using verbal-nominal sentences and active-passive voice in the simple past tense.Keywords: Self-Monitoring Strategy, Simple Past Tense, Self-awareness